Daily life in ancient Egyptian personal correspondence - Thorpe, Susan (Archaeopress Egyptology, 2021)
This publication considers a selection of letters from the Old Kingdom up to and including the Twenty-first Dynasty. Under the topic headings of 'problems and issues', 'daily life', 'religious matters', 'military and police matters', it demonstrates the insight such texts can provide regarding aspects of belief, relationships, custom and behaviour